(untitled) (Scientific journal of the Fergana State University, 2026)
This article analyzes the theoretical foundations that define the content and structure of physical movements. Physical movement is considered the primary form of motor activity of the human body. The article highlights the functions of movements, their psychomotor, biomechanical, and physiological characteristics, as well as their significance in physical education and sports. The structure of movements is viewed as a system comprising spatial, temporal, and force-related components. Accordingly, the article emphasizes the importance of theoretical knowledge in the process of teaching and improving physical movements.